Assessment of knowledge, attitude and practice about diabetes among diabetic patients of tertiary care centre in central India - Nagar, Vivek; Prasad, Pankaj; Mitra, Arun; Kale, Saket; Yadav, Kriti; Shukla, Mukesh (International Journal Of Community Medicine And Public Health, 2018)
Background: Diabetes mellitus (DM) is one of the major fast growing non-communicable disease (NCD) and causes threats to global public health. Prior to initiating an educational program or interventions for diabetic patients, their current level of knowledge (K), attitude (A), and practice (P) should be evaluated. The purpose of this study was thus to determined current diabetes-related knowledge, attitude, and practices (KAP) of adults with Diabetes mellitus.. Methods: Current study was cross sectional study from August to December 2014 in medicine outpatient department of Tertiary care hospital of Bhopal. A semi‑structured interviewer administered questionnaire was used for data collection, and it consisted of four sections. Results: A total of 150 study participants were enrolled for the study. Among them, 58% were male and 425 were female diabetic patients. Around 16% of the participants having good level of knowledge, 34.6% of participants have poor knowledge and 49.3% having moderate knowledge. Out of the total participant 43.3% have positive attitude and only 34% patients had positive practice. Conclusions: In our study most of the patients belong to moderate and poor knowledge score as well as negative practice and negative attitude that emphasizes the need for increasing diabetes awareness activities. The efforts should be more focussed on female patients, younger patients and those who have no family history of diabetes.